EDUCAÇÃO E CIDADANIA AMBIENTAL: PERSPECTIVAS EDUCATIVAS PARA OS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Ribeiro, Carla da Silva (2021)
In this study, the main objective was to understand how environmental education can contribute to the literacy and formation of environmental citizenship of students in the Early Years of Elementary School. The methodological design, with a qualitative approach, comprises a systematic review and a pedagogical intervention, carried out through the application of a Didactic Sequence (SD) of environmental education. The analysis corpus, composed of eight (8) environmental education articles, related to the Early Years, was taken from four (4) national environmental education journals, in the period 2015 to 2019. In this analysis, it was identified which pedagogical practices of environmental education the authors report in these articles. In SD, the purpose was to identify the main conceptions of the environment of the students and also to provide a pedagogical intervention aimed at the formation of literacy and environmental citizenship. The participants of the SD were eleven (11) students, aged between 9 and 10 years old, from two (2) classes of the fourth year of Elementary Education, from a public school in Santa Maria, RS. In this SD, six (6) asynchronous and synchronous activities are presented, by means of remote teaching. The analysis of DS was performed according to the design of Mandalas, by Coutinho et al. (2020), and according to the students' conception of the environment, whose data were analyzed in the light of Bardin's Content Analysis (AC) (2010). The dissertation, written in five complementary chapters, presents, in the first, the regulatory frameworks of Brazilian environmental education and its theoretical assumptions, in which the prerogatives of insertion of environmental education at all levels and teaching modalities are discussed. In the second chapter, environmental knowledge and complexity are pointed out as epistemological foundations of pedagogy and environmental citizenship. The third chapter presents the results of a systematic review on environmental education in the Early Years. The application of a Didactic Sequence of environmental education, developed with children of the 4th year of Elementary Education, from a public school in Santa Maria, RS, is the composition of the fourth part of this research. In the fifth chapter, the discussion of the study was organized, which can be understood as an integrating synthesis of the first four chapters, with the analysis of the research results. Therefore, in this investigation, an innovative perspective is presented in the understanding of environmental education in the Early Years, as a possibility of literacy and the formation of environmental citizenship. With this, it is assumed to contribute to the change of actions, attitudes and habits in relation to nature and it is expected to collaborate so that the present theme is relevant in the context of teacher training courses, since the teacher has an important role in promotion of environmental education in training spaces.